Skeletal muscle dispersion (400‐1000 nm) and kinetics at optical clearing. Issue 1 (26th September 2017) - Oliveira, Luís M.; Carvalho, Maria I.; Nogueira, Elisabete M.; Tuchin, Valery V.
Abstract : Skeletal muscle dispersion and optical clearing (OC) kinetics were studied experimentally to prove the existence of the refractive index (RI) matching mechanism of OC. Sample thickness and collimated transmittance spectra were measured during treatments with glucose (40%) and ethylene glycol (EG; 99%) solutions and used to obtain the time dependence of the RI of tissue fluids based on the proposed theoretical model. Calculated results demonstrated an increase of RI of tissue fluids and consequently proved the occurrence of the RI matching mechanism. The RI increase was observed for the wavelength range between 400 and 1000 nm and for the 2 probing molecules explored. We found that for 30 min treatment with 40% glucose and 99% EG, RI of sarcoplasm plus interstitial fluid was increased at 800 nm from 1.328 to 1.348 and from 1.328 to 1.369, respectively. Abstract : Time dependence for the RI of sarcoplasm plus interstitial fluid (a) and the whole muscle (b) during treatment with 40%‐glucose, showing the RI matching mechanism of optical clearing.